Pengaruh Penggunaan E-Marketplace terhadap Kemampuan Inovasi dan Kinerja (Kasus UKM Furniture, Home Decor dan Kriya) - Susetiyono, Agung; Baihaqi, Imam (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
The use of e-marketplaces in a business will certainly have an impact on innovation capabilities and performance quality. This study aims to gain a better understanding of how e-marketplaces can contribute to innovation capabilities and SME performance. The method used in this study is a quantitative approach with data analysis using Structural Equation Modeling (SEM). Respondents consisted of SME owners or employees who had used e-marketplaces for at least one year and had attended digital marketing training. Data were collected through a questionnaire that measured the variables of e-marketplace usage, innovation capabilities, and performance. The results of the analysis show that e-marketplace usage has a significant positive effect on SME innovation capabilities, and innovation capabilities contribute positively to performance. In addition, this study found that innovation capabilities function as a mediator in the relationship between e-marketplace usage and SME performance. The theoretical implications of this study are to contribute to the development of technology management theory, especially in the context of e-marketplace usage, innovation, and SME performance. Practically, the results of this study can be used as evaluation material and input for SMEs and the government in decision making to improve innovation and performance of furniture, home decor and craft SMEs through the use of e-marketplaces.